Perancangan DC/DC Converter untuk Pembangkit Listrik Tenaga Turbin Angin - Nael Novando (Fakultas Teknik, 2026)
Wind energy is a promising renewable source, but fluctuating wind speed causes unstable voltage output from wind turbine generators, requiring a power electronics circuit to stabilize it. This research designs and implements a DC-DC buck-boost Converter based on incremental PWM control as a voltage stabilizer for a wind turbine power generation system, and analyzes its performance under light (30 W), medium (50 W), and heavy (100 W) load variations at an 18 V reference voltage. The wind source was simulated using a DC motor driVing a DC generator in the laboratory, with an Arduino Uno controlling the duty cycle of an IRF540N MOSFET via an IR2101 driver IC, tested at three input voltages (12 V, 18 V, 24 V) representing boost, transition, and buck modes. Results show the control system maintained Vout regulation close to 18 V across all conditions, with the smallest deviation at medium load. Power conversion efficiency was strongly affected by operating mode: highest at 81.4% in buck mode (Vin 24 V, 50 W load), lowest at 59.3% in boost mode (Vin 12 V, heavy load) due to larger input current and quadratic conduction losses. Overall Converter performance is good and would improve further if the source input voltage is kept high, near or above the reference value.voltage high, near or above the reference value.
Validasi dan Finalisasi Ratna 12 Agustus 2026
Keywords: DC-DC Converter; buck-boost Converter; wind turbine; voltage regulation; power conversion efficiency; PWM